A micro-computed tomographic assessment of oval-shaped root canals obturated with bioceramic sealer using different obturation techniques - Özyürek Taha; Keskin Neslihan Büşra; Aydın Zeliha Uğur (Balkan Stomatological Society, 2022)
Background/Aim: To evaluate void volumes in oval-shaped root canals obturated with three different obturation systems using microcomputed tomography (micro-CT). Material and Methods: Twenty-four distal roots of mandibular molar teeth canals were prepared and randomly divided into three groups (n = 8 in each group). The canals were obturated using single cone (SC), GuttaCore (GC), and warm vertical compaction (WVC) techniques. Each specimen was scanned using a micro-CT device. The volumes of the voids were calculated, and the data were statistically analyzed using a one-way analysis of variance and post hoc Tukey's (P < .05). Results: The void volumes in the WVC group were significantly lower than those in the other groups (P < .05). When different root canal parts were examined, the void volumes increased significantly from the apical to the coronal level in the GC and SC groups (P < .05). In the WVC group, most voids were observed in the middle part (P < .05), whereas there was no significant difference in void volumes in the coronal and apical parts (P > .05). Conclusions: None of the systems provided void-free root filling. However, the void volume using the WVC system was significantly lower than that observed using the other systems.